2015
DOI: 10.2340/00015555-2186
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Integrin α6β4 in the Basement Membrane Zone Lining the Sebaceous Glands in Hidradenitis Suppurativa

Abstract: Hidradenitis suppurativa (HS) is an inflammatory skin disease characterized by painful nodules, abscesses and sinus tracts. The disease is located primarily in the apocrine gland-bearing skin, including the armpits and groins (1). Previous studies have shown that follicular occlusion is present in the majority of patients at an early stage of the disease (2-5); however, the driving mechanism behind this follicular occlusion is unknown. Recently, diminished periodic acid-Schiff (PAS) staining was found in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…However, this study observed significant upregulation of integrins α6 and β4 (signaling molecules with adhesive properties) within the sebaceous gland of HS patients compared to controls. The role of these integrins in HS is unclear at this time 57 .…”
Section: Pathophysiologymentioning
confidence: 89%
“…However, this study observed significant upregulation of integrins α6 and β4 (signaling molecules with adhesive properties) within the sebaceous gland of HS patients compared to controls. The role of these integrins in HS is unclear at this time 57 .…”
Section: Pathophysiologymentioning
confidence: 89%
“…Although the patho genesis of HS is unknown, the role of the cutaneous commensal bacterial community (microbiota) and its potential relationship to the innate immune system in HS appears to be of increasing interest (6)(7)(8)(9). Several studies have hypothesized that a synergistic interaction between the commensal microbiota and aberrant innate immune responses could be a pivotal factor in the pathogenesis of HS (10)(11)(12). However, the structure of the bacterial population, as well as the diversity at strain level, is poorly investigated in patients with HS (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…The increased expression of integrins can be speculated to be either a cause or a consequence of dysbiosis. The findings of Blok et al (1) in the sebaceous glands may therefore indicate an exciting new pathway to pursue in the quest for better understand the complex interplay between bacterial colonization, immunity and structural predisposition of disease.…”
mentioning
confidence: 98%
“…They also play a role in cell growth, proliferation, and may participate in the inflammatory response. In this issue, Blok et al (1), describe the increased expression of integrin α6β4 at the basement membrane zone lining the sebaceous glands in hidradenitis suppurativa (HS), a disease in which much remains to be discovered.…”
mentioning
confidence: 99%